2011
DOI: 10.1371/journal.pone.0020364
|View full text |Cite
|
Sign up to set email alerts
|

The Endoplasmic Reticulum Chaperone Protein GRP94 Is Required for Maintaining Hematopoietic Stem Cell Interactions with the Adult Bone Marrow Niche

Abstract: Hematopoietic stem cell (HSC) homeostasis in the adult bone marrow (BM) is regulated by both intrinsic gene expression products and interactions with extrinsic factors in the HSC niche. GRP94, an endoplasmic reticulum chaperone, has been reported to be essential for the expression of specific integrins and to selectively regulate early T and B lymphopoiesis. In GRP94 deficient BM chimeras, multipotent hematopoietic progenitors persisted and even increased, however, the mechanism is not well understood. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 60 publications
3
44
0
1
Order By: Relevance
“…Previously, we and others found that MZB1 directly associates with the PDI ERp57 and the chaperones BiP and GRP94, suggesting that MZB1 does not act on its own but rather functions in collaboration with folding factors (Shimizu et al 2009;van Anken et al 2009;Flach et al 2010). GRP94 is a substrate-specific chaperone that serves a rather small subset of client proteins, including mHCs, TLRs, and integrins (Melnick et al 1994;Staron et al 2010;Luo et al 2011). Notably, we found that the associations of MZB1 with both GRP94 and mHC are markedly enhanced by induction of a UPR in tunicamycin-treated cells.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, we and others found that MZB1 directly associates with the PDI ERp57 and the chaperones BiP and GRP94, suggesting that MZB1 does not act on its own but rather functions in collaboration with folding factors (Shimizu et al 2009;van Anken et al 2009;Flach et al 2010). GRP94 is a substrate-specific chaperone that serves a rather small subset of client proteins, including mHCs, TLRs, and integrins (Melnick et al 1994;Staron et al 2010;Luo et al 2011). Notably, we found that the associations of MZB1 with both GRP94 and mHC are markedly enhanced by induction of a UPR in tunicamycin-treated cells.…”
Section: Discussionmentioning
confidence: 95%
“…f/f ; Mx-1-Cre mice in a mixed C57BL/6; 129/Sv background were generated, and genotyping was performed as previously described [30]. Littermates that were negative for Cre transgene were used as controls.…”
Section: Grp94mentioning
confidence: 99%
“…Littermates that were negative for Cre transgene were used as controls. Mice that were 5.5 to 6.5 weeks old were subjected to pI.pC-induced deletion of Grp94 primarily in the hematopoietic system performed as previously described [30].…”
Section: Grp94mentioning
confidence: 99%
See 2 more Smart Citations